Aspekter ved samarbeidsrelasjoner mellom erfaringsmedarbeidere og brukere i psykisk helse- og rustjenester: En kvalitativ studie. - Karlsson, Bengt Eirik; Borg, Marit; Ogundipe, Esther; Sjåfjell, Tommy Lunde; Bjørlykhaug, Knut Ivar (Nordisk Tidsskrift for Helseforskning, 2017)
Aspects of collaboration and relationships between peer support workers and service users in mental health and substance abuse services – A qualitative study.Studies have shown that service users report their encounter with peer supporters as positive. However, little is known about service users’ experiences with developing a relationship, working together and collaborate, with peer supporter workers. The aim of this study was therefore, to explore and describe service users’ experiences with peer support relationships, support and collaboration. Twenty-six service users with mental health problems and/or substance abuse voluntarily participated in the study. Data was collected through five focus groups interviews in different areas in Norway. The data was analyzed using a hermeneutic content analysis and resulted in three master themes. Overall, these findings reveal that service users deem their relationship and collaboration with peer supporter workers as positive. Furthermore, these findings offers a critical evaluation of peer support, by highlighting challenges related to peer support relationships and collaboration.